Social support in an effort to increase the husband's willingness to accept vasectomy family planning: KB MOP - Rahmawati, Dechoni; Novitasari, Rahma Kurnia; Kurniawati, Wahyu; Ariningtyas, Ristiana Eka (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The Family Planning (KB) Program is an effort designed by the government to assist married couples in planning the number and distance of child births, using various contraceptive methods. It has a legal basis in the form of Law of the Republic of Indonesia Number 52 of 2009 concerning Population Development and Family Development. The family planning program also has a broader purpose, namely controlling population growth to be more balanced with the availability of resources. As of the first semester of 2024, the number of Indonesia's population has reached 282.477.584 people with a density of 143.73 people per square kilometer. Globally, the Family Planning (KB) program has been recognized as one of the important solutions in suppressing uncontrolled population growth and improving the quality of family life. Purpose: To examine the social support factor on the willingness of the husband as an acceptor of vasectomy family planning. Method: A descriptive correlational, specially focusing on cross-sectional method. The study took place from March 2025 in Senden, Bantul. The independent variable was social support, meanwhile the dependent variable included Husband’s Willingness to Accept Vasectomy. Using random sampling and lame show formula 105 respondents were selected who meet specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using chi square test. Results: There is a significant relationship between social support and the willingness of husbands to accept vasectomy as a method of family planning p-value 0.003. Odd Ratio showed a value of 9.000 which means that people who receive high social support will be 9 times more likely to be willing to be acceptors of family planning MOP than those who receive low social support. Conclusion: Social support can come from various sources, including the wife, family members, peers, and health workers, which can strengthen the husband's confidence and motivation to undergo a vasectomy.